Novel mesoporous SiO 2 conjugated graphene oxide 2D layers: Frequency and temperature dependent dielectric properties - Kumar K.S.; Medhi H.; Banik D.; Suresh M.B.; Borse P.H.; Paik P. (My University, 2025)
In this work, we have synthesized a series of nanocomposites of few layered defective graphene oxide (GO) and mesoporous SiO 2 , and studied their frequency (1–10 MHz) and temperature (50–400 °C) dependent dielectric properties. We have tuned the surface area and pore size of mesoporous SiO 2 and conjugated the mover the GO sheets to achieve new hybrid nanocomposites. The formation of conjugation has been confirmed through microscopy and spectroscopy studies. Impedance spectroscopy indicated a very high dielectric constant for the novel composites that was found to being the range of 7.961 x 10 5 to 2.191 x 10 3 and 2.790 x 10 8 to 2.770 x 10 4 at the frequencies of 1 Hz and 10 kHz at 50 °C and 400 °C, respectively. Such increase in the dielectric constants is attributed to the formation of chemical conjugation on the GO with mesoporous SiO 2 which results due to change in the orientation and space charge polarization as well as the porous behavior of the composites studied at different conditions. Temperature and frequency dependent dc and ac conductivities have also been calculated through the impedance analysis. They were found to be c.a. 0.000 to 0.25 × 10 −3 S/m and 0.007–0.120 S/m, respectively, irrespective of the frequency and temperature for the best composite. We show a very simple and cost effective synthesis in the present study. Further, we engineered new novel new nano composites those display high dielectric constant, by utilizing this approach. Thus, this simple approach can be exploited to tune the desired properties of nanocomposites those can be used in various electronic devices. © 2019